2022
DOI: 10.1136/sextrans-2022-055601
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sexual transmission dynamics and transmission contexts of monkeypox virus: a mixed-methods study of the early outbreak in Belgium (May–June 2022)

Abstract: ObjectiveThe available epidemiological and clinical evidence from the currently ongoing monkeypox (MPX) outbreak in non-endemic areas suggests an important factor of sexual transmission. However, limited information on the behaviour and experiences of individuals with an MPX infection has to date been provided. We aimed to describe the initial phase of the MPX outbreak in Belgium, and to provide a more in-depth description of sexual behaviour and transmission contexts.MethodsWe used routine national surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(35 reference statements)
0
8
0
Order By: Relevance
“… Pooled frequency of genitalia involvement in post-2022 studies. Tarín-Vicente, 2022 [ 27 ], Angelo, 2022 [ 28 ], Betancort-Plata, 2022 [ 29 ], Caria, 2022 [ 30 ], Vanhamel 2022 [ 31 ], Girometti, 2022 [ 33 ], Orviz, 2022 [ 34 ], Hoffmann1, 2022 [ 35 ], Cobos, 2022 [ 36 ], Hoffmann2, 2022 [ 37 ], Van Ewijk, 2022 [ 38 ], Mailhe, 2022 [ 39 ], Nunez, 2022 [ 40 ], Catala, 2022 [ 41 ], Cassir, 2022 [ 42 ], Pascom, 2022 [ 70 ], Suner, 2022 [ 43 ], Maldonado, 2023 [ 44 ]. …”
Section: Figurementioning
confidence: 99%
“… Pooled frequency of genitalia involvement in post-2022 studies. Tarín-Vicente, 2022 [ 27 ], Angelo, 2022 [ 28 ], Betancort-Plata, 2022 [ 29 ], Caria, 2022 [ 30 ], Vanhamel 2022 [ 31 ], Girometti, 2022 [ 33 ], Orviz, 2022 [ 34 ], Hoffmann1, 2022 [ 35 ], Cobos, 2022 [ 36 ], Hoffmann2, 2022 [ 37 ], Van Ewijk, 2022 [ 38 ], Mailhe, 2022 [ 39 ], Nunez, 2022 [ 40 ], Catala, 2022 [ 41 ], Cassir, 2022 [ 42 ], Pascom, 2022 [ 70 ], Suner, 2022 [ 43 ], Maldonado, 2023 [ 44 ]. …”
Section: Figurementioning
confidence: 99%
“…After screening, four qualitative interview-based studies were found to have addressed the question: ‘What are the views and experiences of interventions to prevent sexual transmission of mpox among communities at risk of infection?’ Study characteristics for three cross-sectional [ 32–34 ] and one longitudinal [ 35 ] are given in Table 3 . Two European studies collected data in the initial phases of the outbreak [ 33 , 34 ]; one study in Australia was conducted after the initial outbreak [ 35 ]; and one in China was conducted at a time when reported cases were still increasing [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 32 , 33 , 35 ] only included men (mostly MSM) with experience of mpox. The fourth study [ 34 ] included only MSM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 83 Moreover, the role of networks in the transmission of Monkeypox virus (MPXV) during the early phase of the outbreak in Belgium has been recently described. 84 Pandemics: COVID-19 …”
Section: New Challenges Beyond Known Determinants For Stismentioning
confidence: 99%